Turkey’s Middle Eastern Endeavors: Discourses and Practices of Neo-Ottomanism under the AKP - Özel Volfová, Gabriela (Die Welt des Islams, 2016)
The aim of this research paper is to explain the concept of neo-Ottomanism as a Turkish foreign policy doctrine, as it was formulated by the ruling Justice and Development Party (Adalet ve Kalkınma Partisi, AKP). The paper follows two distinct yet interrelated themes. First, it explains how the neo-Ottoman discourse used by AKP today differs from the civic proto-nationalist discourse of Ottomanism developed by political reformers around 1839–1908, in order to construct an overarching identity formula for the multi-confessional and multi-ethnic Empire which sensed its demise. Second, it discusses the current understanding of neo-Ottomanism in relation to economic, political and cultural interests that the AKP pursues in the Middle East. The argument is that today’s AKP’s interpretation of the Ottoman past as a justification for its growing political, economic and cultural presence in the region is very selective and makes a radical departure from the original 19th century concept. Besides these key analytical concerns, the paper also addresses major changes in Turkish foreign policy, between 2002 and 2013, as well as relevant political transformations in the region. The empirical material consists of documents in both Turkish and English in the form of press releases and public statements of key AKP representatives available online from newspapers, think-tanks, the Republic of Turkey’s Ministry of Foreign Affairs, the Presidency of the Republic of Turkey and AKP websites.